Determining and ranking essential criteria of construction project selection in telecommunication of north Khorasan-Iran - Mojahed, Majid; Mohd Yusuff, Rosnah; Reyhani, Mohammad (International Association of Computer Science and Information Technology, 2010)
Economy project often becomes one of the strong selecting points to attract contractors. However, economy projects sometimes mislead contractors to select. Therefore, it is crucial for contractors to mark projects comparison before deciding to select a smart one. A contractor usually compares some criteria of project but they not enough. The criteria being considered always vary from one contractor to another. Some may only consider the revenue and location, whilst some may focus on its financial of owner, knowledge of supervisor and also revenue of project. Smart contractors might wisely try to include all criteria when evaluating which project is the best one. In this paper two main purposes have been followed. The first purpose is to identify relevant criteria, based on perspective of contractors in North Khorasan Telecommunication. For this reason we will collect some criteria from contractors of construction projects by using Delphi method. To identify achieved criteria, based on view of contractors in North Khorasan Telecommunication-Iran, all contractors of construction came together and discussed about criteria in several sessions. The second purpose of this research is to compute the weighting coefficients and ranking criteria regarding the contractors’ point of view by Comparison Matrix.